The time-varying effects of oil prices on oil-gas stock returns of the fragile five countries - Begüm Yurteri Kösedağlı; Gül Huyugüzel Kışla; A. Nazif Çatik (Financial Innovation, 2021)
This study analyzes oil price exposure of the oil-gas sector stock returns for the fragile five countries based on a multi-factor asset pricing model using daily data from 29 May 1996 to 27 January 2020. The endogenous structural break test suggests the presence of serious parameter instabilities due to fluctuations in the oil and stock markets over the period under study. Moreover, the time-varying estimates indicate that the oil-gas sectors of these countries are riskier than the overall stock market. The results further suggest that, except for Indonesia, oil prices have a positive impact on the sectoral returns of all markets, whereas the impact of the exchange rates on the oil-gas sector returns varies across time and countries.
Keywords: C5; C58; G12; 650; Fragile five; Oil price; Sectoral stock return; Time-varying parameter model